Projected number of people with diagnosed Type 2 diabetes in Germany in 2040. Issue 10 (13th February 2019) - Tönnies, T.; Röckl, S.; Hoyer, A.; Heidemann, C.; Baumert, J.; Du, Y.; Scheidt‐Nave, C.; Brinks, R.
Abstract: Aims: To project the number of people with Type 2 diabetes in Germany between 2015 and 2040. Methods: Based on data from 65 million insurees of the German statutory health insurance, we projected the age‐specific prevalence of diabetes using mathematical relations between prevalence, incidence rate and mortality. We compared several scenarios regarding temporal trends in the incidence and mortality rate. The projected age‐specific prevalence was applied to the projected age structure of the German population between 2015 and 2040 to calculate the number of people with Type 2 diabetes. Results: Application of current age‐specific prevalence estimates to the projected age structure in 2040, although ignoring temporal trends in incidence and mortality, yielded an increase in the number of Type 2 diabetes cases from 6.9 million in 2015 to 8.3 million (+21%) in 2040. More realistic scenarios that account for decreasing mortality rates and different trends in the incidence rates project between 10.7 million (+54%) and 12.3 million (+77%) Type 2 diabetes cases in 2040. Conclusions: For the first time, we projected the number of future Type 2 diabetes cases for the whole adult population in Germany. The results indicate a relative increase in the number of Type 2 diabetes cases of between 54% and 77% from 2015 to 2040. Temporal trends in the incidence rate are the main drivers of this increase. Simply applying current age‐specific prevalence to the future age structure probably underestimates the future number of Type 2 diabetes cases. What's new?: Previous projections of the number of people with Type 2 diabetes in Germany considered only certain age ranges and/or ignored temporal trends in the incidence and mortality rates. This study estimated a relative increase in Type 2 diabetes cases in Germany of between 54% and 77%, resulting in 10.7 million to 12.3 million cases in 2040. Ignoring trends in the incidence and mortality rates severely underestimated the number of Type 2 diabetes cases. There will be increased demand for diabetes healthcare resources and education of specialists in diabetes care, which has likely been underestimated by previous projections.